The success rate of vaginal birth after caesarean section and labour outcomes in women with intrapartum epidural analgesia vs parenteral opioid: preliminary result - Husin, Roziah; Abdulwahab, Dalia F; Awang, Mokhtar (2014)
Introduction: Neuraxial analgesia(epidural), is one of the most effective treatment for labour pain, however this benefit was offset by possible association with increased risk of caesarean section and prolonged labour. The American college of Obstetrician and Gynaecologist recommended delaying the administration of epidural analgesia when possible until cervical dilatation reach at least 4-5 cm, due to increase risk of CS up to 12 folds based on early studies Objective: To compare the effect of epidural with parenteral opioid analgesia on the outcome of labour, successes rates of vaginal birth in women undergoing trial of scar. Method: A prospective study conducted in Hospital Tengku Ampuan Afzan in 2014, all consented women for trial of scar were counselled for either intrapartum epidural or parenteral opioid while in labour with the cervical dilatation of 3-4 cm.